2012
DOI: 10.1038/npp.2012.121
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Inhibitor of κB Kinase Activity in the Nucleus Accumbens on Emotional Behavior

Abstract: Inhibitor of kB kinase (IkK) has historically been studied in the context of immune response and inflammation, but recent evidence demonstrates that IkK activity is necessary and sufficient for regulation of neuronal function. Chronic social defeat stress of mice increases IkK activity in the nucleus accumbens (NAc) and this increase is strongly correlated to depression-like behaviors. Inhibition of IkK signaling results in a reversal of chronic social defeat stress-induced social avoidance behavior. Here, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
58
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(65 citation statements)
references
References 53 publications
6
58
1
Order By: Relevance
“…This evidence builds upon a previously study that demonstrated an antidepressant-like response to acute stress in constitutive IL-6 knockouts and suggests that leukocyte-derived sources of IL-6 may be critical in mediating these behavioral effects (34). Our results are interesting in light of recent studies showing that social defeat stress induces downstream inflammatory signaling pathways, such as NFkB (26,(35)(36)(37), and increases monocyte trafficking (29) throughout a number of CNS structures known to control depression and anxiety behavior. It will be important for future studies to define the brain regions and molecular pathways induced by stress-responsive IL-6 from leukocytes that mediate adverse behavioral responses to chronic stress.…”
Section: Significancesupporting
confidence: 83%
“…This evidence builds upon a previously study that demonstrated an antidepressant-like response to acute stress in constitutive IL-6 knockouts and suggests that leukocyte-derived sources of IL-6 may be critical in mediating these behavioral effects (34). Our results are interesting in light of recent studies showing that social defeat stress induces downstream inflammatory signaling pathways, such as NFkB (26,(35)(36)(37), and increases monocyte trafficking (29) throughout a number of CNS structures known to control depression and anxiety behavior. It will be important for future studies to define the brain regions and molecular pathways induced by stress-responsive IL-6 from leukocytes that mediate adverse behavioral responses to chronic stress.…”
Section: Significancesupporting
confidence: 83%
“…Furthermore, as DFosB is a transcription factor, further studies will be necessary to identify the exact target genes that are regulated by DFosB following antipsychotic drug treatment and delineating which genes are responsible for the various negative behavioral outcomes seen. One established gene target for DFosB in medial PFC is that which encodes the cholecystokinin B receptor (Vialou et al, 2012), which is highly implicated in anxiogenic responses consistent with observations of our studies (Ang et al, 2001;Bowers et al, 2012;Christoffel et al, 2012;McClung and Nestler, 2003). It will now be interesting to use more open-ended approaches to identify many more relevant DFosB target genes.…”
Section: Discussionsupporting
confidence: 76%
“…These changes were correlated with social avoidance behavior [13]. These authors also showed that the social avoidance phenotype and the formation of new stubby spines depended on the inhibitor of kappaB kinase (IkK)-nuclear factor kappaB (NFkB) pathway and that constitutively active IkK was sufficient to promote immature spine synapse formation in mice vulnerable to SDS [14]. …”
Section: Chronic Stress Alters the Number And Function Of Spine Synapsesmentioning
confidence: 99%